(3GdfhQ GdeJdGdi GdeGMi dXdeGJ JhgjGJ GdZRGdi hCgd fMdJgs - (3LeGd GdOjf Ydj Hf YHO Gddg Hf GdbGSe Hf GdeDjO HGddg eMeO GdUfYGfj,J (B1190 (3g` s
(3ChdgG (B:s
(3hHYO aEfg jbhd Ydi Hf YHO Gddg aEfi EWdYJ Ydi JGQjN GHf NdcGf aQCjJ Cf CJhdi GdQO s
(3BNQgG (B:s
(3hQOi ai TeS GdCNHGQ , ai eG LGA ef GdJMPjQ ef GdXde Yf YHO Gddg Hf YjGT s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedcs
(3HBNQgG fbhd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GNJdGa GdabgGAs